PENGARUH BAHASA PENGANTAR PEMBELAJARAN DAN BAHASA IBU TERHADAP HASIL BELAJAR BAHASA JAWA SISWA KELAS III SD SE-KECAMATAN PEJAGOAN - indriyani, jannatun (KALAM CENDEKIA PGSD KEBUMEN, 2014)
ABSTRACT: The purposes of research were to prove: (1) the effect of introduction language learning toward study result of Javanese language on the third grade students of elementary school in the Pejagoan district; (2) the effect of mother tongue toward study result of Javanese language on the third grade students of elementary school in the Pejagoan district; (3) the effect introduction language in learning and mother tongue toward study result of Javanese language on the third grade students of elementary school in the Pejagoan district. The method used was an experimental method with the quantitative approach. The result of the research refer that: (1) there was the different effect of introduction language learning toward result of study of Javanese language on the third grade of elementary school in the Pejagoan district; (2) there was the different effect of mother tongue toward result of study of Javanese language on the third grade of elementary school in the Pejagoan district; (3) there was the different effect of interaction between introduction language learning and mother tongue toward result of study of Javanese language on the third grade of elementary school in the Pejagoan district. Keywords: introduction language learning, mother tongue, result of study of Javanese Language ABSTRAK: Tujuan penelitian adalah untuk membuktikan: (1) ada tidaknya pengaruh bahasa pengantar pembelajaran terhadap hasil belajar bahasa Jawa kelas III SD se-Kecamatan Pejagoan; (2) ada tidaknya pengaruh bahasa ibu terhadap hasil belajar bahasa Jawa kelas III SD se-Kecamatan Pejagoan; (3) ada tidaknya pengaruh bahasa pengantar pembelajaran dan bahasa ibu terhadap hasil belajar bahasa Jawa kelas III SD se-Kecamatan Pejagoan. Metode yang digunakan adalah metode eksperimen dengan pendekatan kuantitatif. Hasil penelitian adalah: (1) ada pengaruh perbedaan bahasa pengantar pembelajaran terhadap hasil belajar bahasa Jawa kelas III SD se-Kecamatan Pejagoan; (2) ada pengaruh perbedaan bahasa ibu terhadap hasil belajar bahasa Jawa kelas III SD se-Kecamatan Pejagoan; (3) ada pengaruh perbedaan dari interaksi antara bahasa pengantar pembelajaran dan bahasa ibu terhadap hasil belajar bahasa Jawa kelas III SD se-Kecamatan Pejagoan. Kata kunci: bahasa pengantar pembelajaran, bahasa ibu, hasil belajar bahasa Jawa